2014
DOI: 10.1002/humu.22496
|View full text |Cite
|
Sign up to set email alerts
|

Tumor Heterogeneity Revealed byKRAS,BRAF, andPIK3CAPyrosequencing:KRASandPIK3CAIntratumor Mutation Profile Differences and Their Therapeutic Implications

Abstract: Current clinical problems in colorectal cancer (CRC) diagnostics and therapeutics include the disease complexity, tumor heterogeneity, and resistance to targeted therapeutics. In the present study, we examined 171 CRC adenocarcinomas from Greek patients undergoing surgery for CRC to determine the frequency of KRAS, BRAF, and PIK3CA point mutations from different areas of tumors in heterogeneous specimens. Ninety two out of 171 (53.8%) patients were found to bear a KRAS mutation in codons 12/13. Of the 126 muta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
38
0
6

Year Published

2014
2014
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(45 citation statements)
references
References 69 publications
0
38
0
6
Order By: Relevance
“…Moreover, BRAF mutation status, as well as KRAS, have been shown to be predictive for whether a patient may benefit to EGFR-inhibitors therapy, such as cetuximab (13). Therefore, detection of these mutations is crucial in the clinical scenario of CRC.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, BRAF mutation status, as well as KRAS, have been shown to be predictive for whether a patient may benefit to EGFR-inhibitors therapy, such as cetuximab (13). Therefore, detection of these mutations is crucial in the clinical scenario of CRC.…”
Section: Introductionmentioning
confidence: 99%
“…The mutation rates of NRAS, in contrast, are lower (1-3%) and activating mutations of HRAS has not been detected in CRC (40,91,92). Previously, pyrosequencing of KRAS, BRAF and phosphatidylinositol-4,5-bisphosphate 3-kinase catalytic subunit α revealed that 53.8% of patients exhibit a KRAS mutation in codons 12 or 13, of which 57.9% were c.38G>A (pG13D), and 22.2% were c35G>T (p.G12V) mutations (93).…”
Section: Krasmentioning
confidence: 99%
“…They also detected tumours harbouring two concomitant KRAS mutations. Other authors have subsequently confirmed these same findings [26][27][28]31]. Based on these studies, it is recommended that tests for RAS status be conducted on metastatic tissue.…”
Section: Laboratory Accreditationmentioning
confidence: 54%
“…However, still a significant proportion of patients selected this way do not respond to therapy. Potential reasons for this, besides alternative resistance mechanisms, may include intratumour heterogeneity [26], differences between the primary tumour and its metastases [27], and the sensitivity of methods used to identify mutations [28].…”
Section: Laboratory Accreditationmentioning
confidence: 99%